2016
DOI: 10.3892/or.2016.4966
|View full text |Cite
|
Sign up to set email alerts
|

β2-adrenergic receptor activation promotes the proliferation of A549 lung cancer cells via the ERK1/2/CREB pathway

Abstract: Abstract. Lung cancer is one of the most common cancers worldwide and accounts for 28% of all cancer-related deaths. The expression of the β 2 -adrenergic receptor (β 2 -AR), one of the stress-inducible receptors, has been reported to be closely correlated with malignant tumors. However, the role of β 2 -AR activation in human lung epithelial-derived cancer A549 cells and the underlying mechanisms are not fully understood. In the present study, we found that activation of β 2 -AR but not β 1 -AR promoted the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…In the context of tumor cells, recent work has demonstrated that CREB can regulate transcription of the MMP‐9 gene via upregulation of Adenylatcyclase 3 (ADCY3) in tumor cells and by activation of the β2‐adrenergic receptor that leads to ERK1/2 and subsequent CREB phosphorylation and enhanced MMP‐9 transcription . By using ERK1/2 inhibitor U0126, the authors showed that, similarly to our work, CREB activation occurs downstream of ERK1/2, as ERK1/2 inhibition abolished CREB activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of tumor cells, recent work has demonstrated that CREB can regulate transcription of the MMP‐9 gene via upregulation of Adenylatcyclase 3 (ADCY3) in tumor cells and by activation of the β2‐adrenergic receptor that leads to ERK1/2 and subsequent CREB phosphorylation and enhanced MMP‐9 transcription . By using ERK1/2 inhibitor U0126, the authors showed that, similarly to our work, CREB activation occurs downstream of ERK1/2, as ERK1/2 inhibition abolished CREB activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to behavioural and social patterns, one might speculate that the physiological stress response itself could play a role in the association between poor stress resilience and lung and liver cancer occurrence; adrenergic signalling pathways have for example been suggested in the carcinogenic process of lung cancer 30. Psychological stress exposure in individuals with low stress resilience has been proposed to entail an exaggerated cardiovascular stress response due to amplified cognitive interpretations of stressful events 8.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of β-AR activation is cell-specific as β 2 -AR antagonists and agonists have been demonstrated to attenuate cell growth. For example, β-ARs activation may promote cell proliferation of certain cancer cells including lung cancer cells (20), ovarian carcinoma (5), human hepatocellular carcinoma cells (30), pancreatic (31), prostate (32), gastric (33) and colorectal cancer cells (34). By contrast, several studies have demonstrated that the β-AR agonist ISO suppresses the proliferation of MDA-MB-231 human breast cancer cells (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular viability was measured using the MTT assay as described previously (20). Briefly, cells were seeded in flat-bottomed 24-well plates (5x10 4 cells/well) and grown for 24 h in DMEM supplemented with 10% FBS.…”
Section: Rt-quantitative Pcr (Qpcr)mentioning
confidence: 99%